RHYME STRUCTURE OF CONTEMPORARY ARUZI POEMS (Scientific journal of the Fergana State University, 2024)
In this article, rhyme is considered one of the main aspects of art in our classical poetry. The creativity of the creator is determined by the significance of the rhymes used in the poems in revealing the essence of ideas, the image of symbols, the spiritual depth, melodiousness, brilliance and charm of the words chosen for the rhyme. The appropriate use of various types and arts of rhyme, weight and rhyme relations is considered one of the important aspects of the poet's skill. That's why every creator has carefully studied the science of rhyme